Fostering critical thinking through intervention in teaching and learning in the classroom - Kaminsky, Suritha (Peninsula Technikon, 2012)
Thesis (MTech (Education))--Peninsula Technikon, Cape Town, 2004. === The purpose of this research was to investigate the practices, understanding and application of critical thinking in the lives of learners, educators and parents. The research was conducted in the grade seven classes of three schools in the Western Cape. These schools are representative of the demography of the Western Cape. Initial questionnaires were sent to parents of the grade seven learners in this study to determine whether the home environment encourages critical thinking and whether or not the parents practice critical thinking in their home and personal lives. An interview was conducted with the 8 teachers of each grade seven class at the three schools, to determine their understanding of critical thinking, whether they use critical thinking in their personal capacity, and whether they nurture and teach critical thinking. Each learner completed a questionnaire to determine his or her knowledge and understanding of critical thinking, prior to teaching and learning interventions. The interventions occurred through a series of teaching/learning activities, and participative action research to facilitate the learning, understanding and application of critical thinking. Data was obtained from observation throughout intervention as well as from a final questionnaire at the end of the teaching/ learning activities. The data collected was analysed and the results and recommendations form part of this thesis. The results clearly indicated that it is possible to foster critical hoped that teachers' awareness of the need to teach and foster critical thinking in the classroom was aroused by this intervention. thinking through teaching and learning interventions. It also became evident that the influence of learners' home life plays a major role in children's thinking practices. It is hoped that teachers' awareness of the need to teach and foster critical thinking in the classroom was aroused by this intervention. === Peninsula Technikon